Survey and inventory of threatened plant species in Ha Giang province, Vietnam - Tai, Vu Anh; Thin, Nguyen Nghia (Academia Journal of Biology, 2015)
Our survey and inventory of the threatened plant species have been carried based on Vietnam Red Data Book (2007) for all of the plant species existed in Ha Giang province. The total of 156 plant species belonging to 66 vascular plant families were identified and listed in Vietnam Red Data Book (2007), which is 36.6% of the total threatended species of Vietnam’s flora, of those 1 species seems to be extinct in the wild, 13 critically endangered species, 61 endangered species and 81 vulnerable species (one variaty). Additionally, the total 88 threatened species of 36 families recorded for the flora in Ha Giang province. This result can serve as the scientific basis for the plant biodiversity conservation of Ha Giang province.